2020
DOI: 10.3390/polym12081829
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biocomposite Polymeric Systems Loaded with Antibacterial Nanoparticles for the Coating of Polypropylene Biomaterials

Abstract: The development of a biocomposite polymeric system for the antibacterial coating of polypropylene mesh materials for hernia repair is reported. Coatings were constituted by a film of chitosan containing randomly dispersed poly(d,l-lactide-co-glycolide) (PLGA) nanoparticles loaded with chlorhexidine or rifampicin. The chlorhexidine-loaded system exhibited a burst release during the first day reaching the release of the loaded drug in three or four days, whereas rifampicin was gradually released for at least 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The authors showed the cellular internalization with intracellular cytoplasmic localization and preserved fluorescence and necrosis affinity for Hyp-NPs, suggesting their potential applications in tumor imaging and therapy [86]. Fernández-Gutiérrez and coworkers reported the fabrication of a biocomposite polymeric system for the antibacterial coating of polypropylene mesh materials for hernia repair [87]. Figure 4(a)-(d) shows the microscopic and scanning electron microscopic (SEM) images of the meshes with different coatings.…”
Section: Nanomedicinementioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed the cellular internalization with intracellular cytoplasmic localization and preserved fluorescence and necrosis affinity for Hyp-NPs, suggesting their potential applications in tumor imaging and therapy [86]. Fernández-Gutiérrez and coworkers reported the fabrication of a biocomposite polymeric system for the antibacterial coating of polypropylene mesh materials for hernia repair [87]. Figure 4(a)-(d) shows the microscopic and scanning electron microscopic (SEM) images of the meshes with different coatings.…”
Section: Nanomedicinementioning
confidence: 99%
“…The antibacterial coating was performed by a film of chitosan containing poly(D,L-lactide-co-glycolide) (PLGA) nanoparticles loaded with antibiotic (rifampicin) or an antiseptic (chlorhexidine). Both biocomposite coatings exhibited antibacterial activity and cell compatibility, offering a potential strategy to protect meshes from bacterial adhesion following implantation [87].…”
Section: Nanomedicinementioning
confidence: 99%
“…Chitosan has been widely employed in tissue engineering and biomedical applications due to its biocompatibility, biodegradability, and antimicrobial activity [147][148][149][150]. Normally, chitosan is crosslinked using genipin or glutaraldehyde by a chemical crosslinking mechanism [151].…”
Section: Chitosan Based Bioinksmentioning
confidence: 99%
“…Therefore, it is indispensable to study how to prolong and control the release time of drugs. Fernandez-Gutierrez et al 55 coated PP mesh with a film of CS containing randomly dispersed PLGA nanoparticles loaded with rifampicin. Experiments demonstrated that the coatings with rifampicin were gradually released over no less than 11 days and effectively precluded bacterial colonization of mesh.…”
Section: Strategies For Reducing Postoperative Complicationsmentioning
confidence: 99%